2013
DOI: 10.1177/000348941312200303
|View full text |Cite
|
Sign up to set email alerts
|

Hyoid Bone Syndrome: A Retrospective Review of 84 Patients Treated with Triamcinolone Acetonide Injections

Abstract: Hyoid bone syndrome should be considered in patients who present with throat pain. Injection of triamcinolone into the affected greater cornu can confirm the diagnosis and resolve symptoms. A positive response to triamcinolone injection may obviate the need for additional testing and procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 10 publications
4
26
1
6
Order By: Relevance
“…The shortened thyrohyoid distance, as demonstrated by patients in this cohort, was hypothesized to be the source of pain by Counter et al Potential causes include friction between the superior cornu of the thyroid cartilage and hyoid bone, shortened distance between the hyoid bone and thyroid cartilage or impingement of an enlarged greater horn of the hyoid bone on the cervical spine, or abnormal bone formation in the thyrohyoid ligament . Stern et al demonstrated histopathologic evidence of microscopic foci of necrosis within the hyoid bone at points of contact and friction . Finally, Ernest et al showed hyaline chaining of centrally placed multiple nuclei and elongation of muscle fibers consistent with myopathy of middle pharyngeal constrictor muscle in hyoid bone syndrome .…”
Section: Discussionmentioning
confidence: 67%
“…The shortened thyrohyoid distance, as demonstrated by patients in this cohort, was hypothesized to be the source of pain by Counter et al Potential causes include friction between the superior cornu of the thyroid cartilage and hyoid bone, shortened distance between the hyoid bone and thyroid cartilage or impingement of an enlarged greater horn of the hyoid bone on the cervical spine, or abnormal bone formation in the thyrohyoid ligament . Stern et al demonstrated histopathologic evidence of microscopic foci of necrosis within the hyoid bone at points of contact and friction . Finally, Ernest et al showed hyaline chaining of centrally placed multiple nuclei and elongation of muscle fibers consistent with myopathy of middle pharyngeal constrictor muscle in hyoid bone syndrome .…”
Section: Discussionmentioning
confidence: 67%
“…9 We can assume that the excess strain placed on the laryngeal ligaments and muscles, via the Lombard effect, has contributed to an insertion tendonitis on the hyoid bone. Stern et al 10 have recently described a high prevalence of dysphonia (51%) in patients with hyoid bone syndrome. Their article accounts for this finding as a secondary result of pain from the hyoid bone tendonitis, leading to increased muscle tension from a ''guarding'' effort to reduce pain.…”
Section: Discussionmentioning
confidence: 99%
“…A second possible mechanism for pain persistence is cartilaginous or ligamentous inflammation involving the laryngeal framework. This includes hyoid, thyrohyoid, thyroid ligament, and cricoid syndromes depending on the location of the pain . Most patients have pain triggered or accompanied by swallowing or strenuous neck movement, with a subset reporting pain precipitated by excessive voice use.…”
Section: Discussionmentioning
confidence: 99%
“…This includes hyoid, thyrohyoid, thyroid ligament, and cricoid syndromes depending on the location of the pain. [16][17][18] Most patients have pain triggered or accompanied by swallowing or strenuous neck movement, with a subset reporting pain precipitated by excessive voice use. A third possible mechanism is myofascial pain involving the intrinsic and extrinsic laryngeal muscles as described by Jung et al 6 A fourth possible mechanism for pain persistence is suggested by the failure sometimes of localized injections to achieve long-term pain relief.…”
Section: Possible Mechanismsmentioning
confidence: 99%